Digital Technology as a Driver of Improved Regional Development - Gulmira NURGAZINA; Sergei YEROKHIN; Lilia MATRAEVA; Sofia VORONTSOVA (Communications of International Proceedings, 2021)
The article deals with modern trends in the economy's transition to a new technological mode, which requires the formation of relevant approaches to organizational and economic support of production processes, as well as management systems and methods. The relevance of this topic is due to the need to increase the competitiveness of Russian enterprises, to increase labor productivity, to reduce production costs.
Keywords: Innovation; Digital Technology; National Competitiveness; Efficiency.